Difficulties Faced by Students and Teachers in Online Teaching Process During Covid-19 in Lalbandi Municipality (Geographical Journal of Nepal, 2023)
This paper analyzes the difficulties faced by the students and teachers in online teaching learning process during the COVID-19 pandemic. Online learning is an alternative platform that replaced to the face-to-face mode of instruction. It refers to instruction that is delivered electronically through various multimedia, internet platforms and applications. This paper is based on mixed-method research design and primary and secondary data sources are used. Primary data were collected from field observation, personal interviews with students, teachers, parents, and focus group discussion. In this process, two secondary schools which were involved in online learning were purposively selected from Lalbandi Municipality of Sarlahi district of Madhesh Pardesh. Secondary data were collected from various sources- journals, Municipal offices, and e-resources. The findings show that online-learning has been felt more reliable mode of instruction during the pandemic situation for students, teachers and parents. However, it faces a lot of problems during operation and it became ineffective as compared to face-to-face mode of instruction. It is mainly due to the lack of electronic devices to support online class, lack of high-speed internet facility, irregular power supply, lack of teacher-students' interaction and ineffective assignment practices. As a result, a large number of students have not participated in online learning. Thus, this paper concludes that a strong institutional support policy among schools and local government requires to mainstreaming students participation in online-class.